MENTAL REVOLUTION TO INCREASE ECONOMIC INDEPENDENCE AND NATION’S COMPETITIVENESS OF SURAH AR-RA’D VERSE 11 PERSPECTIVE - Witro, Doli; Yanti, Betria Zarpina; Rasidin, Mhd. (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
Observing the reality of the Indonesian nation, which could be said to be in an appalling economic condition, it seems that the desire to do what is known as the Mental Revolution must be intensified. Mental revolution is considered as an alternative solution to the various crisis problems that have plagued this nation, especially concerning economic independence and national competitiveness. Through a mental revolution, the Indonesian nation is believed to be able to rediscover the lost humanity and the starting point for building a new society or a better civilization. In this paper, the author wants to describe the economic independence revolution as an essential part that needs attention in the implementation of the mental revolution program currently being run by the government. This is based on the reality of Indonesian society, which is still shackled by a mentality of a low work ethic, not creative, not innovative, rough work, lazy, and even still adhering to the principle of working a little, the results (money) a lot. In analyzing this problem, the writer explains it based on the analysis of the letter ar-Ra’d verse 11. This verse gives a clue that Allah will not change the economic condition of a country, as long as that country does not change the cause of its economic setback. Likewise, if a nation changes its state from immorality to obedience, then Allah will change his condition from misery to happiness.
Keywords: Mental Revolution; Economic; National Competitiveness; al-Ra’d; Morality